2019
DOI: 10.1093/mnras/stz1677
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the jet parameters of active galactic nuclei using Bayesian analysis of VLBI data with a non-uniform jet model

Abstract: Physical parameters of AGN jets observed with Very Long Baseline Interferometry (VLBI) are usually inferred from the core shift measurements or flux and size measured at a peak frequency of the synchrotron spectrum. Both are preceded by modelling of the observed VLBI jet structure with a simple Gaussian templates. We propose to infer the jets parameters using the inhomogeneous jet model directly -bypassing the modelling of the source structure with a Gaussian templates or image deconvolution. We applied Bayesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…In the general case of arbitrary exponents 𝑚, 𝑛 and optically thin spectral index 𝛼 analytical expressions for the distribution of optical depth and brightness temperature can be found in, e.g. Pashchenko & Plavin (2019). Lobanov (1998) has shown that the relativistic jet model can be used to estimate the jets physical parameters, e.g.…”
Section: Jet Model and Core Shift Measurementsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the general case of arbitrary exponents 𝑚, 𝑛 and optically thin spectral index 𝛼 analytical expressions for the distribution of optical depth and brightness temperature can be found in, e.g. Pashchenko & Plavin (2019). Lobanov (1998) has shown that the relativistic jet model can be used to estimate the jets physical parameters, e.g.…”
Section: Jet Model and Core Shift Measurementsmentioning
confidence: 99%
“…However, this requires some further assumptions because core shift measurements alone do not constrain the parameters of the jet model. More on degeneracies between model parameters can be found in Pashchenko & Plavin (2019). The most widely used is the assumption of an equipartition between emitting particles and magnetic field energy densities (Lobanov 1998;O'Sullivan & Gabuzda 2009;Pushkarev et al 2012).…”
Section: Jet Model and Core Shift Measurementsmentioning
confidence: 99%
See 3 more Smart Citations